Annular urticarial lesions - Örnek, Sinem; Zuberbier, Torsten; Kocatürk, Emek (Clinics in dermatology, 2022)
Annular urticarial configurations are often associated with acute and chronic urticaria. Such lesions may be short-lived, migratory, transient, pruritic, and resolving with no residual evidence, making the diagnosis of urticaria an obvious one. Annular urticarial lesions can be the presenting signs of various cutaneous and systemic diseases. The differentiation of urticarial lesions may be made by considering the duration of an individual lesion longer than 24 hours, with burning and pain sensation in the lesions or lack of pruritus; skin marks such as postinflammatory pigmentation or purpura after resolution of the lesions; associated scaling or vehiculation in the lesions; systemic symptoms such as arthralgia, fever or fatigue; and several abnormal laboratory findings. The main differential diagnoses of annular urticarial lesions include urticarial vasculitis, autoinflammatory syndromes, hypersensitivity reactions, and connective tissue diseases.